Compounds used to produce cloned animals are genotoxic and mutagenic in mammalian assays in vitro and in vivo - Oliveira, R.j.; Mantovani, M.s.; Da Silva, A.f.; Pesarini, J.r.; Mauro, M.o.; Ribeiro, L.r. (Associação Brasileira de Divulgação Científica (ABRADIC), 2014)
The compounds 6-dimethylaminopurine and cycloheximide promote the successful production of cloned mammals and have been used in the development of embryos produced by somatic cell nuclear transfer. This study investigated the effects of 6-dimethylaminopurine and cycloheximide in vitro, using the thiazolyl blue tetrazolium bromide colorimetric assay to assess cytotoxicity, the trypan blue exclusion assay to assess cell viability, the comet assay to assess genotoxicity, and the micronucleus test with cytokinesis block to test mutagenicity. In addition, the comet assay and the micronucleus test were also performed on peripheral blood cells of 54 male Swiss mice, 35 g each, to assess the effects of the compounds in vivo. The results indicated that both 6-dimethylaminopurine and cycloheximide, at the concentrations and doses tested, were cytotoxic in vitro and genotoxic and mutagenic in vitro and in vivo, altered the nuclear division index in vitro, but did not diminish cell viability in vitro. Considering that alterations in DNA play important roles in mutagenesis, carcinogenesis, and morphofunctional teratogenesis and reduce embryonic viability, this study indicated that 6-dimethylaminopurine and cycloheximide utilized in the process of mammalian cloning may be responsible for the low embryo viability commonly seen in nuclear transfer after implantation in utero.
Keywords: Somatic cell nuclear transfer; 6-Dimethylaminopurine; Cycloheximide; Genotoxic; Mutagenic